An edible oil packaging film with improved barrier properties and heat sealability from cassia gum incorporating carboxylated cellulose nano crystal whisker. (January 2020) - Cao, Lele; Ge, Tingting; Meng, Fansong; Xu, Shiyu; Li, Jian; Wang, Lijuan
Abstract: A cassia-gum (CG) based edible packaging film was reinforced with carboxylated cellulose nano crystal whisker (C-CNCW), which is a potential alternative for oil-bags. The effects of C-CNCW dosage on the films were investigated by analyzing the rheological property of the film-forming solutions, the mechanical, barrier, thermal stability and heat sealability of the films. The C-CNCW with a zeta potential of −48.5 mV was a long silk-like structure with the diameter of 3–10 nm. Rheological results manifested that all the film-forming solutions exhibited a shear thinning property and the addition of C-CNCW changed the interaction of CG chains. The FTIR results showed that no new chemical bonds formed between CG and C-CNCW. SEM indicated that the aggregation of C-CNCW occurred at the content of 6%. The addition of C-CNCW reduced the light transmittance from 63.43% to 51.91% at 500 nm, but improved the oil permeability, mechanical properties, and heat seal strength from 0.550 to 0.064 g mm m −2 day −1, 18.53–32.85 MPa and 1295.40–2218.78 N/m as the C-CNCW dosage increased from 0% to 4%, respectively. Therefore, CG film reinforced by C-CNCW is promising in oil packaging. Graphical abstract: Image 1 Highlights: Cassia gum (CG)/carboxylated cellulose nano crystal whisker (C-CNCW) film was gained. The film-forming solutions exhibited a shear-thinning property. The addition of C-CNCW enhanced the heat sealability and mechanical properties. The CG/C-CNCW film has lower oil permeability. The CG/C-CNCW film is a potential alternative to plastic films for oil bag.